PEMODELAN SISTEM INFORMASI PRAKTIK BAIK STANDAR PROSES PEMBELAJARAN STMIK AKI PATI - Khoirul Anwar; Listiarini Edy Sudiati; Ninik Haryani (LPPM Politeknik Saint Paul Sorong, 2023)
Based on Article 1 Point 20 of Law No. 20/2003 concerning the National Education System, it is stated that learning is a process of interaction between students and educators and learning resources in a learning environment. In the higher education environment, this interaction occurs between students and lecturers. This learning process does not only consist of lecturers and students, but also methods or learning strategies that will be used by lecturers in the learning process, learning objectives to be achieved and learning materials. This study aims to build a model of a standard good practice information system for the learning process at STMIK AKI Pati, because the process of monitoring and evaluating learning so far is still using a manual system. The system development method used is the Rapid Application Development method